A Nutty Study: A Framing Analysis of the 2009 Salmonella Outbreak in Peanut Products - Erica Goss Irlbeck; Cindy Akers; Ashley Palmer (Journal of Applied Communications, 2011)
The purpose of this study was to examine television news coverage of the 2009 Salmonella outbreak in peanut products through the scope of framing theory. The aim of this research was to understand how the television news media frame agricultural, particularly food safety, messages. By employing a qualitative content analysis, researchers analyzed television news transcripts from ABC, CBS, CNN, and NBC that aired during the peanut product recall. The frames found from this research were informational, anti-Peanut Corporation of America, and anti-FDA. The most commonly used sources were victims of Salmonella, politicians, and current and former FDA off icials. No agricultural frames were present, and the only agricultural organizations interviewed were one representative of the Georgia Department of Agriculture and Ag Secretary Tom Vilsack. The researchers concluded that sources did not appear to have a large impact on the way the news was covered for this study. The researchers also found a need for more scientific food safety information to be communicated to the national media.
Keywords: anti-Peanut Corporation of America; anti-FDA; agricultural; Salmonella; safety information